A review of the empirical measures on becoming a mother and their relevance to the American Indian/Native Alaskan mother: implications for research and policy. Issue 2 (4th March 2022) - Maxwell, December; Leat, Sarah R.
ABSTRACT: American Indian/Alaska Native (AI/NA) mothers are at an increased risk for postpartum mental health disorders. One risk factor for developing a disorder is maladaptive beliefs about becoming a mother (BAM). The maternal role transition is measured using scales that often assess the risk of developing postpartum depression (PPD). AI/AN women have had their motherhood historically marginalized through forced sterilizations and the removal of their children. As such, a review of the literature is warranted to evaluate the validity of BAM measures with AI/AN populations. This review included 36 studies and assessed BAM measures for reliability and validity. Only five studies included AI/AN populations. As such, this review indicates BAM measurements have not been used reliably with AI/AN populations. Further research needs to be conducted to understand the culturally specific mothering practices of AI/AN mothers before BAM measures can be used to assess postpartum mental health disorders for this population.